Role of Brown and Beige Adipose Tissues in Seasonal Adaptation in the Raccoon Dog (Nyctereutes procyonoides) - Niiranen Laura; Mäkelä Kari A; Mutt Shivaprakash J; Viitanen Riikka; Kaisanlahti Anna; Vicente David; Noponen Tommi; Autio Anu; Roivainen Anne; Nuutila Pirjo; Saarela Seppo; Herzig Karl-Heinz (Switzerland, 2022)
Brown adipose tissue (BAT) expresses uncoupling protein-1 (UCP1), which enables energy to be exerted towards needed thermogenesis. Beige adipocytes are precursor cells interspersed among white adipose tissue (WAT) that possess similar UCP1 activity and capacity for thermogenesis. The raccoon dog (Nyctereutes procyonoides) is a canid species that utilizes seasonal obesity to survive periods of food shortage in climate zones with cold winters. The potential to recruit a part of the abundant WAT storages as beige adipocytes for UCP1-dependent thermogenesis was investigated in vitro by treating raccoon dog adipocytes with different browning inducing factors. In vivo positron emission tomography/computed tomography (PET/CT) imaging with the glucose analog 18F-FDG showed that BAT was not detected in the adult raccoon dog during the winter season. In addition, UCP1 expression was not changed in response to chronic treatments with browning inducing factors in adipocyte cultures. Our results demonstrated that most likely the raccoon dog endures cold weather without the induction of BAT or recruitment of beige adipocytes for heat production. Its thick fur coat, insulating fat, and muscle shivering seem to provide the adequate heat needed for surviving the winter.